Corporate governance, the long-term orientation and the risk of financial distress - evidence from european private equity backed leveraged buyout transactions - Marini, Vladimiro; Caratelli, Massimo; Barbaraci, Ilaria (Piccola Impresa / Small Business, 2019)
We study whether Private Equity sponsors are long-term oriented with their Leveraged Buyout (LBO) European targets after the euro-crisis. Their reputational constraints could incentivize them to value capture rather than value creation. Since LBOs are highly levered and LBO sponsors intervene in the corporate governance (CG), their orientation is measured by looking at how CG mechanisms affect portfolio companies’ Risk of Financial Distress (RFD). We find that LBO sponsors make a better use of CG mechanisms to mitigate RFD than other forms of ownership; however, results do not allow to exclude value capture.